Farm-scale trials to compare the entomopathogenic fungus Beauveria bassiana with pirimiphos methy + deltamethrin and essential oil of lemon grass for protection of stored cowpea against Callosobruchus maculatus (Coleoptera: Bruchidae) - Cherry, A.J.; Abalo, P.; Hell, K.; Korie, S. (Wiley, 2007)
In trials conducted in Benin, conidia of Beauveria bassiana were evaluated as a control method against the cowpea weevil, Callosobruchus maculatus, in stored cowpea. In the first trial using a high artificial infestation of C. maculatus in 8-kg batches of cowpea in jerry cans under typical conditions, concentrations of 1 × 109 and 1 × 1011 conidia kg−1 were compared with lemon grass oil at 2 mL kg−1 and the synthetic pesticide mixture of 1.5% pirimiphos methyl + 0.05% deltamethrin at 0.5 g kg−1. After 2 months of storage, seed losses (SD) were 20.63 (5.3)% in the untreated control, 8.04 (3.2)% in the low-dose B. bassiana group, 3.12 (1.3)% in the high-dose B. bassiana group, 2.52 (0.4)% in the lemon grass oil group and 0% in the pirimiphos methyl + deltamethrin group. In a second trial with natural infestations in 50-kg batches of cowpea in 200-L drums, treatment with B. bassiana 1 × 1011 conidia kg−1 was compared with pirimiphos methyl + deltamethrin at 0.5 g kg−1. After 6 months of storage on six farms, losses reached 30.76 (1.5)% in the control, 1.28 (0.2)% in the pirimiphos methyl + deltamethrin group and 3.69 (0.6)% in the B. bassiana group.